Analysis of Mutations in Epidermal Growth Factor Receptor Gene in Korean Patients with Non-small Cell Lung Cancer: Summary of a Nationwide Survey - Lee, Sang Hwa; Kim, Wan Seop; Choi, Yoo Duk; Seo, Jeong Wook; Han, Joung Ho; Kim, Mi Jin; Kim, Lucia; Lee, Geon Kook; Lee, Chang Hun; Oh, Mee Hye; Kim, Gou Young; Sung, Sun Hee; et al. (Journal of pathology and translational medicine, 2015)
Analysis of mutations in the epidermal growth factor receptor gene (EGFR) is important for predicting response to EGFR tyrosine kinase inhibitors. The overall rate of EGFR mutations in Korean patients is variable. To obtain comprehensive data on the status of EGFR mutations in Korean patients with lung cancer, the Cardiopulmonary Pathology Study Group of the Korean Society of Pathologists initiated a nationwide survey. We obtained 1,753 reports on EGFR mutations in patients with lung cancer from 15 hospitals between January and December 2009. We compared EGFR mutations with patient age, sex, history of smoking, histologic diagnosis, specimen type, procurement site, tumor cell dissection, and laboratory status. The overall EGFR mutation rate was 34.3% in patients with non-small cell lung cancer (NSCLC) and 43.3% in patients with adenocarcinoma. EGFR mutation rate was significantly higher in women, never smokers, patients with adenocarcinoma, and patients who had undergone excisional biopsy. EGFR mutation rates did not differ with respect to patient age or procurement site among patients with NSCLC. EGFR mutation rates and statuses were similar to those in published data from other East Asian countries.